Coronavirus: A threat to Global Public Health - Singh, Soni; Singh, Anil Kumar; Jain, Pankaj Kumar; Singh, Naresh Pal; Kumar Bajpai, Prasant; Kharya, Pradip (Indian Journal of Community Health, 2020)
Previously considered of meagre significance to the human race, coronaviruses have effectively evolved to jump the species barrier and cause widespread contagion in mankind. The SARS pandemic, the MERS situation in the middle-east and the ongoing COVID 2019 epidemic are all attributed to this evolving virus. COVID 2019 is the seventh coronavirus isolated successfully and the third beta-coronavirus that causes a fatal illness in humans; the other two beta-coronaviruses being severe acute respiratory syndrome (SARS) CoV and middle east respiratory syndrome (MERS) CoV. Having a natural reservoir in bats these viruses infect humans through an intermediate host and then rapidly adapt and mutate for human to human transmissions. Four other known alpha coronaviruses cause only common cold in humans. Although mortality rate of COVID 2019 epidemic is lower at 2.5% than the previous two CoV outbreaks, that is, 9.6% in SARS and 34.4% in MERS, but rapid transmissibility points towards a sustained epidemic of epic proportions. In the absence of any specific treatment protocols and experimental vaccines still under research, management largely depends upon symptomatic therapy, strict infection control and quarantine measures. Restriction of human interactions with known animal sources of the virus as a measure of prevention is essentially required. Owing to huge genetic diversity and frequent genomic recombination, novel coronaviruses might emerge periodically, warranting the need for extensive research and development of effective treatments and vaccines.